PENGARUH PERSEPSI HARGA, CITRA MEREK, TERHADAP KEPUTUSAN DAN KEPUASAN PELANGGAN KOPI JAGO - Vika Nurul Fajeri; Meylani Tuti (LPPM Universitas Asa Indonesia, 2025)
This study aims to analyze the influence of price perception and brand image on purchasing decisions and their impact on customer satisfaction for Kopi Jago products. This study uses a quantitative approach, data were collected through distributing questionnaires to respondents who have purchased Kopi Jago. The sampling technique used was Accidental Sampling with a total of 255 respondents. The data analysis technique used SEM-PLS through the SmartPLS 3 application. The results of the study indicate that both price perception and brand image have a positive and significant effect on purchasing decisions and customer satisfaction. In addition, purchasing decisions have also been shown to have a significant effect on customer satisfaction. These findings confirm that positive perceptions of price and a strong brand image can increase purchasing decisions and customer satisfaction. Kopi Jago needs to continue to maintain quality, image, and competitive prices to maintain and increase customer satisfaction.